Prolonged latency of preterm prelabour rupture of membranes and neurodevelopmental outcomes: a secondary analysis. (31st May 2016) - Drassinower, D; Friedman, AM; Običan, SG; Levin, H; Gyamfi‐Bannerman, C
Abstract : Objective: To determine whether prolonged latency after preterm prelabour rupture of membranes (PPROM) is associated with an increased risk for adverse neurodevelopmental outcomes. Design: This is a secondary analysis of the randomised controlled trial of magnesium sulphate for the prevention of cerebral palsy. Setting: Multicentre trial. Population: A total of 1305 women with PPROM were analysed, 1056 of whom had an interval of <3 weeks between diagnosis and delivery and 249 of whom had an interval of ≥3 weeks between diagnosis and delivery. Methods: We evaluated whether the time interval between diagnosis of PPROM and delivery was associated with an increased risk for adverse neurodevelopmental outcomes. Latency was analysed as a continuous variable and categorised by weeks of latency. Main outcome measures: The primary outcome was motor and mental Bayley scores of <70 at 2 years of age. Secondary outcomes included motor and mental Bayley scores <85 and mean Bayley scores. Logistic regression was used to control for confounding factors. Results: In the univariate analysis, motor and mental Bayley scores of <70 were similar in the <3 weeks (16.8 and 14.4%) and ≥3 weeks (15.3 and 14.1%) groups. In the regression analysis adjusting for confounding factors, PPROM for ≥3 weeks was an independent risk factor for motor (adjusted odds ratio (aOR) 2.12; 95% confidence interval, 95% CI 1.29–3.49) and mental (aOR 1.83, 95% CI 1.13–3.00) Bayley scores of <70. Neonatal sepsis, gestational age at delivery, maternal education, and race were significantly associated with neurodevelopmental outcomes. Conclusions: Whereas delivery at later gestational age is associated with improved prognosis for many outcomes, prolonged exposure to an intrauterine environment of PPROM is an independent risk factor for adverse neurodevelopmental outcomes. Tweetable abstract: Prolonged PPROM was associated with motor and mental Bayley scores of <70. Tweetable abstract: Prolonged PPROM was associated with motor and mental Bayley scores of <70.